Incidence of acute undifferentiated febrile illnesses in an urban slum of Delhi: A longitudinal cohort study - Debadatta Nayak; Roja Varanasi; Abhinav Sinha; Rajiv Janardhanan; Simran Tandon; Sanghamitra Pati (Elsevier, 2024)
Objective: Acute undifferentiated febrile illness (AUFI) is a neglected topic in health care. It has considerable morbidity and mortality worldwide. Slum dwellers are at high risk due to poor living conditions. This longitudinal cohort study estimated the incidence of AUFI in urban slum dwellers in Delhi. Methods: This study was conducted on urban slum dwellers in Delhi. Data were collected using a structured interviewer-administered questionnaire over a period of 18 months. Adjusted incidence rates (IR) and incidence rate ratios (IRR) were calculated using Poisson regression models. Kaplan-Meier survival curves were used to estimate survival from fever. Results: A total of 1497 population were studied. Incidence rate of AUFI was 47.43 per 1000 person-months (95% CI: 44.88; 50.08). The incidence was highest among the 50-59 year age group (54.18 per 1000 person months; 95% CI: 43.19; 67.17). Significant seasonal variation was observed with IR high in winter (IR: 32.80 per 1000 person month; adjusted IRR: 1.44 (95% CI: 1.26; 1.66) and monsoon (IR:19.89 per 1000 person month; adjusted IRR: 0.44 (95% CI: 0.36; 0.53). Conclusion: This study has shown a high incidence rate of AUFI amongst the slum dwellers in Delhi. This calls for awareness about clinical investigation and management among patients and healthcare providers. The findings from this study may sensitize policymakers and healthcare stakeholders to draw a road map with insightful consideration of the environmental factors that bring health burdens to the slum population. Further, comparative studies between slum and non-slum dwellers may be undertaken to evaluate the incidence of AUFI.